1989
DOI: 10.1017/s0031182000059114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a genetic cross between Trypanosoma brucei rhodesiense and T. b. brucei

Abstract: Two trypanosome clones, representing East and West African homozygotes at 2 isoenzyme loci (T. b. rhodesiense MHOM/ZM/74/58 [CLONE B] and T. b. brucei MSUS/CI/78/TSW 196 [CLONE A]), were cotransmitted through tsetse flies and the resulting trypanosome populations checked for the presence of non-parental karyotypes by pulsed-field gel electrophoresis. Ten clones isolated from these populations proved to have 5 different recombinant genotypes by analysis of nuclear and kinetoplast DNA (kDNA) polymorphisms. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 34 publications
8
66
0
Order By: Relevance
“…On the other hand, blots with the CP probe as well as some of the ethidium bromide stained PFGE gels revealed the existence of non-parental size chromosomes in some of the hybrid progeny. This phenomenon was observed previously (Gibson, 1989) and further investigation is required to elucidate the mechanism. …”
supporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, blots with the CP probe as well as some of the ethidium bromide stained PFGE gels revealed the existence of non-parental size chromosomes in some of the hybrid progeny. This phenomenon was observed previously (Gibson, 1989) and further investigation is required to elucidate the mechanism. …”
supporting
confidence: 69%
“…Analysis of the chromosomes detected by the cysteine proteinase gene probe for progeny clones -IA and -ID is also consistent with these hybrids inheriting one homologue from each parent; however, progeny clones -IB and -IC show a novel nonparental karyotype which, without further data, is difficult to interpret conclusively. Results which indicate that homologous chromosomes can differ in size have been provided by other authors Gibson, 1989;Gottesdiener etal. 1990) but the mechanisms by which these size differences arise remain to be elucidated.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In contrast to the salivarian trypanosomes (Gottesdiener^a/. 1990;Gibson, 1989;Gibson, Garside & Bailey, 1992) the chromosomes of Megatrypanum species range in size from 22 Mb to 300 kb and do not appear to have an abundant class of minichromosomes. Although we cannot exclude the presence of chromosomes of much larger size than 2-2 Mb due to the retention of DNA in the sample slot of the PFGE-gels, all attempts to resolve chromosomes above this size using methods which have proved successful with chromosomes from salivarian trypanosomes have been unsuccessful (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Extensive molecular and biochemical analysis have indicated that while T. b. gambiense isolates are homogeneous over most of their wide geographic distribution, T. b. rhodesiense isolates are heterogeneous, showing high genotypic variation within and between different disease foci. [5][6][7][8][9] Various analytical methods such as isoenzyme analysis and restriction fragment length polymorphism (RFLP) have revealed great heterogeneity in both T. b. rhodesiense and T. b. brucei, but have not defined clear criteria for differentiation between these two subspecies. Therefore, new genetic tools are required to discriminate between trypanosomes within the animal reservoirs and the insect vector, and between those that infect humans and those that are not infectious.…”
Section: Introductionmentioning
confidence: 99%